Feasibility Analysis of the Sorong Special Economic Zone (SEZ) Location, Provinsi Papua Barat Daya - Tajuddin, Tamrin; ibal, la; Masniar, Masniar (Jurnal Geografika (Geografi Lingkungan Lahan Basah), 2024)
Government Regulation Number 31 of 2016 designated the Sorong Special Economic Zone (KEK) as the first Special Economic Zone in Papua. The establishment of the Sorong SEZ is expected to become a new center of economic growth in eastern Indonesia, in line with one of the principles of Nawacita, namely building Indonesia from the outskirts. This study employs the analysis of location feasibility, environmental feasibility, technical feasibility, and financial feasibility. The variables of this study are slope, land use, flood-prone, landslide-prone, and suitability of spatial pattern, as well as environmental feasibility, land use, flood-prone, landslide-prone, spatial planning, environment, technical, and economic and financial. The location of the Sorong SEZ in Provinsi Papua Barat Daya is based on the overlay with the Sorong Regency RTRW, most of the Sorong SEZ is an industrial area with a mostly gentle slope, not included in the landslide-prone area, but has a fairly high flood-prone area. Environmental feasibility dictates that the Sorong SEZ area is located in a coastal/beach area, thereby prohibiting companies from using groundwater as a raw water source for their operations. The existence of infrastructure such as the 50 MW PLN Power Plant, Arar Port, clean water network, and others makes the Sorong Special Economic Zone technically qualified as the Sorong Special Economic Zone. The Sorong Economic Zone Development Financing Plan, based on its economic and financial feasibility, provides the following details: The plan includes initial preparation costs of IDR 1,124,659,690,000, infrastructure costs of IDR 236,390,000,000, general facility costs of IDR 235,315,000,000, and basic infrastructure costs of IDR 800,000,000,000.